Measures to improve patient needs assessments and reduce practice variation in Dutch home care organizations. Issue 5 (12th December 2022) - Schwenke, Marit; van Dorst, José; Zwakhalen, Sandra; de Jong, Judith D.; Brabers, Anne E. M.; Bleijenberg, Nienke
Abstract: Aim: Worldwide, long‐term care tends to shift from institutional care towards home care. In order to deliver high‐quality and adequate care, the type, amount and cost of care is determined by a patient needs assessment. However, there are indications that this patient needs assessment varies between comparable patients. In the Netherlands, some home care organizations aim to improve patient needs assessments by implementing improvement measures to reduce this practice variation. The goal of this study was to explore the type and perceived impact of those implemented improvement measures. Design: A cross‐sectional explorative survey study was conducted among Dutch home care organizations between January and April 2021. Methods: An online questionnaire with 26 items was developed by the research team, which was distributed through Dutch nationwide home care sector organizations, the Dutch nurses' association (V&VN) and the Dutch society for home care nursing (NWG). Results: The survey was completed by 184 respondents, including home care nurses, managers and staff who are responsible for training, policy and quality of care. Intervision and peer review for home care nurses were the most common reported improvement measures that were implemented in home care organizations. The experiences of those improvement measures have been perceived as creating greater uniformity in the patient needs assessment, making home care nurses feel more supported and secure performing their patient needs assessment and that the provided care is more in line with patients' demand. Our findings give insights into type and perceived impact of improvement measures that Dutch home care organizations implemented. Further research is needed to find out whether improvement measures actually improve patient needs assessments and reduce practice variation.